Sanksi Tindakan Dalam Hukum Pidana di Indonesia Perspektif Teori Relatif - Uni Sabadina (UIR Law Review, 2025)
Abstract: This study aims to analyze the position and regulation of action sanctions (maatregel) in the Indonesian criminal law system from the perspective of Relative Criminal Theory. The research method used is normative juridical through literature studies of laws and regulations and legal literature. The results of the study show that although theoretically Indonesia's criminal law adheres to a double track system that places criminal sanctions (straf) and equivalent action sanctions, in the practice of legislation and law enforcement, action sanctions are still positioned as number two and are less accommodated. Traditional criminal sanctions (such as imprisonment) remain the "primadonna" due to the legacy of retributive thinking and public perceptions that think punishment should be retaliative. In fact, from the perspective of Relative Theory, sanctions for actions that are rehabilitative and preventive are considered more effective in improving perpetrators and protecting the community in the long term. The excessive dominance of criminal sanctions has proven ineffective, characterized by high recidivism rates and overcapacity of correctional institutions. The conclusion of this study is that legislation policy reform is needed to better integrate and equalize action sanctions, as well as a paradigm shift among law enforcement and society to shift from a retributive approach to a more rehabilitative and preventive approach in accordance with the principles of Relative Theory. Keywords: Action Sanctions, Relative Theory, Criminal Law, Double Track System, Rehabilitation.